PROBLEM BASED LEARNING TO ENHANCE STUDENTS' CRITICAL THINKING SKILLS AND CONCEPT COMPREHENSION IN POLLUTION CONCEPT - Hardianni, Mitha (2013)
This research paper which entitled "Problem Based Learning to Enhance Students' Critical Thinking Skills and Concept Comprehension in Pollution Concept" is conducted due to traditional learning which is more focus on students' academic achievement rather than the process of contructing the knowledge and students' thinking skill in solving their problem. Thus, the main objectives of this research are to investigate the enhancement of students' critical thinking skill and concept comprehension trough Problem Based Learning approach also to investigate students response toward Problem Based Learning. Research method that used in this reserach is quantitative descriptive method with one group pretest and posttest design. Population of this research are 10 grade of high school students in one of international school in Tanggerang. While the sample of this reseach are choosen by using purposive sampling method. the sample chosen are 10 grade students in lower achievement class. According to the result of this reseach indicates that there is enhancement of students' critical thinking skill with normalized gain index value is as much as 0.33 which include in medium category. Students enhancement of concept comprehension in this reseach are analyed in each subtopic and each cognitive domain. The subtopic that most reached by students is soil pollution with normalized gain index value is 0.75 which include in high category. Meanwhile, the highest enhancement in cognitive domain are understanding aspect (C2) and evaluating aspect (C5) with normalized gain index value is 0.57 which include in medium category. Furthermore in students response, mostly students gave positive response toward science and Problem Based Learning. Keyword: Problem Based Learning, Critical Thinking Skill, Concept Comprehension